E-Book Utilization among Library and Information Science Students at Universitas Negeri Padang through the iPusnas Application - Putri Nurhaliza; Marlini (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The increasing adoption of digital libraries has expanded access to electronic learning resources in higher education; however, university students’ utilization of e-books through Indonesia’s National Digital Library application, iPusnas, remains underexplored. This study aimed to analyze the utilization of e-books through iPusnas among undergraduate students in the Library and Information Science Program at Universitas Negeri Padang. A descriptive quantitative approach was employed, involving 56 students selected through simple random sampling. Data were collected using a questionnaire based on the five dimensions of the Technology Acceptance Model and analyzed using descriptive statistics. The findings revealed that students demonstrated positive perceptions across all dimensions, indicating that iPusnas facilitates information retrieval and supports academic activities. Nevertheless, several practical limitations continued to affect its actual utilization. The study concludes that iPusnas has substantial potential as a digital learning resource in higher education. These findings contribute empirical evidence regarding students’ acceptance and utilization of a national digital library platform and provide practical implications for improving digital collections, system usability, and user-oriented library services.